A TWO-YEAR ANALYSIS OF UTERINE RUPTURE IN PREGNANCY - Islam, Ansa; Shah, Azmat Ali; Jadoon, Humaira; Fawad, Aneesa; Javed, Maria; Abbasi, Aziz-un Nisa (Journal of Ayub Medical College Abbottabad, 2019)
Background: Uterine rupture, an obstetrical emergency though rare but still has grave implications. Uterine rupture is the occurrence of breach in the wall of uterus. Complete rupture involves complete disruption of uterine wall resulting in spillage of uterine contents into the abdominal cavity whereas an incomplete rupture has intact peritoneum or serosa. The most commonly reported risk factor in developed countries is previous caesarean section whereas in developing countries neglected and obstructed labour are more frequently reported predisposing factors. Methods: This was a cross sectional descriptive study which was carried out for a period of 2 years from January 2015 to December 2016 in Gynae A unit of Ayub Teaching Hospital Abbottabad. Results: In our study frequency of uterine rupture was 0.63%. Previous scar dehiscence was the most common risk factor for uterine rupture. Maternal mortality was 4% out of total 52 ruptured uterus, while 94.2% was perinatal mortality. Conclusion: Although uterine rupture can be prevented but its frequency is still high. Therefore, proper antenatal care, health education, utilisation of health facilities is needed to reduce adverse outcome associated with this avoidable condition. Keywords: Uterine Rupture; Scarred uterus; Fetomaternal outcome; perinatal mortality; risk factors